Seed Biology Updates – Highlights and New Discoveries in Seed Dormancy and Germination Research - Nonogaki, Hiroyuki (Frontiers in Plant Science, 2017)
An understanding of the biology of seeds has been greatly advanced in recent years. The progresses, particularly in the field of seed dormancy and germination research, have been made at a remarkable speed. Some of the possible epigenetic mechanisms, including an involvement of non-coding RNA, which were predicted for DELAY OF GERMINATION1 just a few years ago, have now been demonstrated with strong molecular and genetic evidence. Imprinting, or parent-of-origin-specific gene silencing/expression, which was characterized particularly for developing seeds, was also found in imbibed seeds and suggested for dormancy mechanisms. Hormone biology in seeds, which is the most advanced and almost a traditional area of seed research, also presents a new dimension. Upstream regulators of hormone metabolism and hormone transporters, such as ABA and GA influx/efflux carriers, have been identified. Characterization of the novel posttranslational modification pathways, including the N-end rule and S-nitrosylation pathways, which play a critical role in turnover of the major hormone signal transduction proteins, also expanded our knowledge about the complexity of hormone signaling in seeds. These progresses made at the molecular level are significant steps toward a better understanding of how seeds translate soil and other environmental signals into their internal hormone biology and make an important decision to stay dormant or commence with germination.